2018
DOI: 10.1007/s10926-018-9799-1
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Content of the Vocational Advice Intervention and Training Package for the Study of Work and Pain (SWAP) Trial (ISRCTN 52269669)

Abstract: Purpose There are substantial costs associated with sickness absence and struggling at work however existing services in the UK are largely restricted to those absent from work for greater than 6 months. This paper details the development of an early Vocational Advice Intervention (VAI) for adult primary care consulters who were struggling at work or absent due to musculoskeletal pain, and the structure and content of the training and mentoring package developed to equip the Vocational Advisors (VAs) to delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…This paper has detailed the iterative development throughout the course of a large-scale programme, of clinician support to deliver a complex intervention in the context of an RCT, and as such, can be a valuable practical resource for researchers developing future primary care interventions. There is a wealth of literature on the development of theory-informed interventions that aim to change clinician behaviour, with varying results (see, for instance: [24][25][26][27]). Much of this literature focuses on development of behaviour change interventions themselves, and on evaluating clinicians' and patients' uptake and engagement [28][29][30]; and this research has highlighted some similar challenges to those identified here, including the practical and time issues involved in engaging clinicians, and the challenge of achieving clinician 'buy in' .…”
Section: Discussionmentioning
confidence: 99%
“…This paper has detailed the iterative development throughout the course of a large-scale programme, of clinician support to deliver a complex intervention in the context of an RCT, and as such, can be a valuable practical resource for researchers developing future primary care interventions. There is a wealth of literature on the development of theory-informed interventions that aim to change clinician behaviour, with varying results (see, for instance: [24][25][26][27]). Much of this literature focuses on development of behaviour change interventions themselves, and on evaluating clinicians' and patients' uptake and engagement [28][29][30]; and this research has highlighted some similar challenges to those identified here, including the practical and time issues involved in engaging clinicians, and the challenge of achieving clinician 'buy in' .…”
Section: Discussionmentioning
confidence: 99%
“…The SVAI is an adaptation of the vocational advice intervention developed for the SWAP trial [ 12 ]. The intervention emphasizes the identification and problem solving of modifiable health and work-related obstacles to RTW [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SVAI is an adaptation of the vocational advice intervention developed for the SWAP trial [ 12 ]. The intervention emphasizes the identification and problem solving of modifiable health and work-related obstacles to RTW [ 12 ]. The main adaption made to the intervention in the MI-NAV study was that the participants were stratified into two risk groups before random allocation (low/medium or high-risk for long-term sick leave) [ 13 ] and follow-up was customised according to risk group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiotherapists will receive monthly mentoring during the intervention period by the course instructor (GS) and two of the researchers (FA and AT). The SVAI is based on the SWAP trial from the UK [23], but delivered as a stratified intervention (see below) and adapted to fit a Norwegian context. The intervention emphasizes the assessment and problem solving of modifiable health and work-related obstacles to RTW, in collaboration with key stakeholders.…”
Section: Interventionsmentioning
confidence: 99%